Short report : adult Aedes abundance and risk of dengue transmission - Ong, Janet (2021)
Dengue is transmitted mainly by the adult female Aedes aegypti mosquito. However, little is known about the impact of adult Aedes abundance on the risk of dengue transmission. Here we analysed nationally representative dengue case and vector surveillance data collected from Singapore, to determine the effect of adult Aedes abundance on the risk of dengue transmission. A case was an area with active dengue transmission as indicated by the presence of dengue cluster. A control was an area where no dengue cluster was reported. Using multivariate logistic regression, we analysed 88 cases and 602 controls and estimated the odds of dengue cluster formation at various adult Aedes abundance levels, estimated by the mean number of adult female Aedes per Gravitrap per week and categorised into Low, Moderate, High and Very High abundance level. We found that the risk of dengue cluster formation was positively associated with adult Ae. aegypti abundance. We observed a three to four-fold increase in the odds of dengue clusters forming in areas with High (AOR: 3.40, 95% CI: 2.09, 5.52) and Very High (AOR: 3.99, 95% CI: 2.46, 6.46) adult Aedes aegypti abundance level compared to those with low Ae. aegypti abundance level. Our study strengthens the evidence for the use of adult Aedes indices for dengue risk assessment and early warning for dengue outbreaks. Entomological indicators of adult Ae. aegypti could be used to anticipate and prioritize areas for dengue control.